Indene-1, 3-dionemethylene-4H-pyran derivatives containing alkoxy chains of various lengths: aggregation-induced emission enhancement, mechanofluorochromic properties and solvent-induced emission changes. Issue 14 (8th October 2015) - Liu, Yanze; Lei, Yunxiang; Li, Fei; Chen, Jiuxi; Liu, Miaochang; Huang, Xiaobo; Gao, Wenxia; Wu, Huayue; Ding, Jinchang; Cheng, Yixiang
Abstract : Indene-1, 3-dionemethylene-4 H -pyran derivatives exhibiting alkoxy-chain-length-dependent optical properties. Abstract : A series of D–π–A indene-1, 3-dionemethylene-4 H -pyran (IDMP) derivatives with aggregation-induced emission enhancement phenomena were synthesized using indene-1, 3-dionemethylene as an electron acceptor and a phenyl ring containing different lengths of alkoxy chains as an electron donor. The as-synthesized IDMP solids emit from red to yellow fluorescence and the fluorescence emissions show obvious blue shifts with the increase of the length of the alkoxy chains. Some of these compounds exhibit obvious redshift mechanofluorochromic (MFC) properties, and the longer the alkoxy chain, the more remarkable the MFC properties. Moreover, the fluorescence emission of these compounds can be switched by using various external stimuli such as grinding, annealing, and solvent fuming. In particular, solvent-induced emission changes similar to those resulting from MFC properties can be achieved by a simple dissolution–desolvation process in different solvent systems, such as chloroform and THF. X-ray diffraction experiments reveal that the MFC properties and solvent-induced emission changes can both be considered as altered-morphology-induced emission properties, which are ascribed to the transformation between the crystalline and amorphous states. The results indicate that the subtle manipulation of the length of the alkoxy chain of IDMP derivatives could endow them with unique and tunable solid-state optical properties.